Public Health Center Emergency Referral Quality Analysis: Based on National Standard - Sasmito, Priyo; Prasetya, Fika Indah; Yektiningtyastuti, Yektiningtyastuti; Rasmita, Dina; Amsyah, Ummul Khairi; Ahmadi, Ahmadi; Aljufri, Salim; Librianty, Nurfanida (PT Inovasi Pratama Internasional, 2024)
The referral quality will affect the outcome of referred patients. The quality of emergency referrals from the Public Health Center (PHC) in Banten Province has not been examined. This study aims to analyze the quality of emergency referrals from PHC and the factors that influence it. Observational analytics with a retrospective approach to a PHC in Banten Province, Indonesia. The reference data for March-May 2023 is taken consecutively. Data on the demographics of referrers and referral cases are recorded. The quality of referrals is analyzed using national personal referral standards. A total of 52 referral cases were involved in the study. Referrals were made by nurses with an average age of 28.2 years with a range of 23-43 years, men (38/73.1%), and with diploma education (30/57.7%). Most of the referring nurses have a valid Basic Life Support (BLS) certificate (46/88.5), are non-civil servants, and work for an average of 3.3 years. Most of the referred cases are surgical (28/53.8) and urgency cases (32/61.5). Forty-four referral cases (84.6%) did not meet national referral standards. The referring nurse's educational background and the urgency of the case had a significant relationship with the quality of referrals with p values < α values of 0.05 (0.000 and 0.000 respectively). There was no significant relationship between referral quality and patient/family satisfaction. Conclusion: Most PHC's emergency referrals to hospital emergency departments (ED) have not complied with national standards. There was a significant relationship between the education of the referring nurse and the level of urgency of the case with the quality of PHC referrals. There is no relationship between referral quality and patient/family satisfaction. National technical guidelines for individual referrals for emergency cases are needed.